(untitled) (Global Journal of Management and Business Research, 2012)
Community is the basic existence mode to the human being, the connotation of community shall be defined from community subject to community life. The current police mechanism management has changed gradually from traditional police mechanism to modern police mechanism; community fits the guidance of modern police mechanism philosophy to campus police mechanism management better in China. The attribute of campus police mechanism community includes three aspects, i.e., community relationship, community function and community category. The attribute of community has decided the construction approach to the campus police mechanism community. To cultivate the common ethics of campus police mechanism is the important measure of achieving the community relationship#x2019;s mutual aid attribute. To establish the multiparty participation mechanism is the basic safeguard to achieve the community function#x2019;s self sufficiency attribute. To promote the collaboration extent of campus police mechanism is the necessary content of the community category#x2019;s pluralism attribute.